The Effect Of Product Design And Product Quality On Consumer Satisfaction In Micro, Small And Medium Enterprises (Msmes) In Denpasar, Bali - Khairunnisak, Khairunnisak; Gusviany Ayu Murti (Journal Of Management Analytical and Solution (JoMAS), 2022)
The purpose of this study is to analyze the effect of product design and product quality on consumer satisfaction at MSMEs in Denpasar, Bali. This study uses a descriptive type of research with a quantitative approach. The sampling technique was random sampling using a questionnaire. Respondents in this study amounted to 100 respondents who are MSME consumers in Denpasar, Bali. The analytical method used is SPSS 21 with multiple linear regression analysis. The results of this study indicate that all hypotheses have a positive and significant effect.